Antibacterial and antifouling ceramic product glaze and preparation method thereof

By using the composite technology of silver nitrate, europium nitrate and gadolinium nitrate in ceramic glazes, as well as the combination of sodium cocoate and specific silicon materials, the problem of poor antibacterial and antifouling effects of ceramic glazes is solved, and the glaze is achieved with excellent antibacterial and antifouling properties.

CN119612962AInactive Publication Date: 2025-03-14CHAOZHOU XIONGMEI CERAMICS IND CO LTD

Patent Information

Application Number
CN202411840683.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The glazes of existing ceramic products are not effective in antibacterial and anti-fouling, resulting in the surface of ceramic products being prone to adsorbing dirt and bacteria, affecting hygiene and durability.

Method used

A glaze preparation method is adopted, which is mainly silver nitrate and supplemented by europium nitrate, and stimulates the activity of silver and europium ions through gadolinium nitrate, combines sodium cocoate to form a steric hinder effect, and adds dimethoxymethyl (3,3,3-trifluoropropyl) silicon and polysiloxane to enhance antifouling performance.

Benefits of technology

It significantly improves the antibacterial and anti-fouling effect of ceramic glaze, ensures that the surface of ceramic products has excellent antibacterial and anti-fouling properties, extends service life and improves hygiene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187900500000021
    Figure BDA0005187900500000021
  • Figure BDA0005187900500000022
    Figure BDA0005187900500000022
  • Figure BDA0005187900500000051
    Figure BDA0005187900500000051
Patent Text Reader

Abstract

The invention relates to an antibacterial and anti-fouling ceramic product glaze and a preparation method, and belongs to the technical field of ceramic product glaze preparation, the ceramic product glaze comprises the following raw materials: a component A: a base material, a water glass solution, a sodium bicarbonate solution, a gadolinium nitrate solution, a europium nitrate solution, a silver nitrate solution and sodium cocoate; and the component B comprises the following components: dimethoxy methyl (3, 3, 3-trifluoropropyl) silicon, polysiloxane, dodecenyl succinic anhydride, gamma-methacryloxy propyl trimethoxy silane and white gasoline. Silver nitrate serves as a main material, europium nitrate serves as an auxiliary material, gadolinium nitrate excites the activity of silver and europium ions, and the silver nitrate, the europium nitrate and the gadolinium nitrate cooperate, so that the prepared ceramic product glaze has excellent antibacterial performance; sodium cocoate is added to form a steric hindrance effect, so that agglomeration among system particles is inhibited, and the antibacterial property of the glaze is enhanced; according to the anti-fouling glaze disclosed by the invention, the dimethoxymethyl (3, 3, 3-trifluoropropyl) silicon and the polysiloxane are added, so that the prepared glaze has a lasting anti-fouling effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic product glaze preparation, and in particular, relates to an antibacterial and antifouling ceramic product glaze and a preparation method thereof. Background Art

[0002] Antibacterial and antifouling is an important research direction in the field of ceramic glaze technology. Its purpose is to make the surface of ceramic products have antibacterial and antifouling functions by changing the chemical composition and microstructure of the glaze, thereby improving its durability and hygiene. In addition, the antibacterial and antifouling technical background of ceramic glazes mainly stems from people's demand for high-quality ceramic products. The surface of traditional porcelain on the market is easy to absorb dirt and bacteria, and it is difficult to clean, and it is easy to breed bacteria and mold, which poses a potential threat to human health. In addition, if it is used for daily ceramic tableware, medical equipment, sanitary ware, etc., it is easy to cause the risk of cross infection, which is extremely unfriendly to people's health. Therefore, it is particularly important to provide a ceramic glaze with excellent antibacterial and antifouling effects. Summary of the invention

[0003] The purpose of the present invention is to provide an antibacterial and antifouling ceramic glaze and a preparation method thereof. Silver nitrate is mainly used, europium nitrate is supplemented, and gadolinium nitrate is used to stimulate the activity of silver and europium ions. The three work together to make the prepared ceramic glaze have excellent antibacterial properties; sodium cocoate is added to form a steric hindrance effect, which inhibits the agglomeration of system particles and strengthens the antibacterial property of the glaze; dimethoxymethyl (3,3,3-trifluoropropyl) silicon and polysiloxane are added to make the prepared glaze have a lasting antifouling effect; and the problem of weak antibacterial and antifouling effects of the prior art ceramic glaze is solved.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] An antibacterial and antifouling ceramic glaze, the ceramic glaze comprising the following raw materials in parts by weight:

[0006] Component A:

[0007]

[0008] Component B:

[0009]

[0010] As a preferred embodiment of the present invention, the base material in component A includes potassium feldspar, sodium feldspar, dolomite, quartz and calcined talc.

[0011] As a preferred embodiment of the present invention, the mass ratio of potassium feldspar, sodium feldspar, dolomite, quartz and calcined talc is 20-35:18-30:7-18:15-20:6-9.

[0012] As a preferred embodiment of the present invention, the concentrations of the water glass solution and the sodium bicarbonate solution are both 10-20wt%; the concentration of the gadolinium nitrate solution is 0.005-0.008mol / L, the concentration of the europium nitrate solution is 0.03-0.05mol / L, and the concentration of the silver nitrate solution is 0.05-0.07mol / L.

[0013] As a preferred embodiment of the present invention, the method for preparing the ceramic product glaze comprises the following steps:

[0014] S1, mixing the base material and deionized water uniformly, ball-milling, and sieving to obtain a pretreated base material;

[0015] S2, preheating three quarters of the weight of the water glass solution and the sodium bicarbonate solution in a temperature-controlled water bath, mixing the two after the preheating is completed, and then stirring at a controlled temperature and speed to obtain a mixed solution A;

[0016] S3, preheating the remaining water glass solution and sodium bicarbonate solution in a temperature-controlled water bath, then adding the preheated water glass solution and sodium bicarbonate solution to mixed solution A with stirring to obtain mixed solution B and adjusting the pH of mixed solution B, then sequentially adding pretreated base material, silver nitrate solution, europium nitrate solution, gadolinium nitrate solution and sodium cocoate with controlled speed stirring to obtain mixed solution C, which is the finished product of component A;

[0017] S4, controlling the temperature and stirring white oil, dimethoxymethyl (3,3,3-trifluoropropyl) silicon, γ-methacryloxypropyl trimethoxysilane, polysiloxane and dodecenyl succinic anhydride to obtain a finished product of component B.

[0018] As a preferred embodiment of the present invention, in step S1, the mass ratio of the base material to the deionized water is 5-5.5:2-2.5; the mass of the balls in the ball mill is 3.5-5 times the mass of the base material; and the screening is through a 200-mesh sieve with a sieve residue ≤15%.

[0019] As a preferred embodiment of the present invention, the temperature of the temperature-controlled water bath preheating in step S2 is 80-90°C and the time is 3-5min; the temperature-controlled and speed-controlled stirring is specifically to control the temperature at 70-95°C and the speed at 400-500r / min and stir for 20-25min.

[0020] As a preferred embodiment of the present invention, the temperature of the temperature-controlled water bath preheating in step S3 is 80-90°C and the time is 3-5 minutes; the stirring speed of adding the preheated water glass solution and sodium bicarbonate solution to the mixed solution A is 100-200 r / min and the stirring time is 5-10 minutes.

[0021] As a preferred embodiment of the present invention, the pH of the mixed solution B in step S3 is adjusted by dropping nitric acid to adjust the pH of the mixed solution B to 5-6; the speed of the controlled stirring is 150-200 r / min, and the time is 0.5-1h.

[0022] As a preferred embodiment of the present invention, the temperature of the temperature-controlled stirring in step S4 is 35-50° C. and the time is 10-20 min.

[0023] As a preferred embodiment of the present invention, the application of the ceramic product glaze is as follows: first, component A of the ceramic product glaze is subjected to conventional processes to prepare glaze slurry, spray glaze, and dry, and then fired into a kiln to form a ceramic semi-finished product; the ceramic semi-finished product is evenly sprayed with component B of the ceramic product glaze at room temperature and allowed to stand for 48-52 hours to obtain a finished ceramic product.

[0024] Beneficial effects of the present invention:

[0025] (1) The present invention uses water glass solution and sodium bicarbonate solution as raw materials to prepare white carbon black, adds gadolinium nitrate, europium nitrate and silver nitrate to modify the white carbon black, and obtains a white carbon black antibacterial agent with excellent antibacterial performance. Specifically, silver nitrate is used as the main component and europium nitrate is used as the auxiliary component, and the antibacterial ability of silver and europium metals is used for compounding. Silver destroys the proliferation ability of bacteria in a short time to induce cell death, and europium destroys the sheath and wall structure of bacteria to make the bacteria lose their original functions. At the same time, the coordination effect of gadolinium nitrate produces a certain stimulating effect on the activity of silver and europium ions, so that the activity of silver and europium ions is increased and it is easier to be adsorbed by white carbon black. At this time, the interaction force between silver and europium ions on the surface of white carbon black is enhanced, thereby increasing the antibacterial performance of the modified white carbon black. That is, the three components of gadolinium nitrate, europium nitrate and silver nitrate work together to make the prepared ceramic product glaze have excellent antibacterial performance.

[0026] (2) The sodium cocoate added in the present invention forms a micellar structure to wrap the white carbon black in the system, forming a steric hindrance effect. At the same time, it also prevents the white carbon black particles from forming a complete water film, and the liquid bridges between the particles disappear, which hinders the adsorption of water by the white carbon black, thereby inhibiting the agglomeration of the white carbon black particles, making it uniformly antibacterial, and further enhancing its antibacterial performance.

[0027] (3) The present invention adds dimethoxymethyl (3,3,3-trifluoropropyl) silicon and polysiloxane, so that the polysiloxane can penetrate and deposit into the micropores on the surface of the ceramic glaze prepared using the present invention. At the same time, a cross-linking reaction occurs in the system to generate a cross-linked body with a certain hardness and good wear resistance, which can effectively resist the action of external forces and thus achieve a long-lasting anti-fouling effect. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] An antibacterial and antifouling ceramic glaze, the ceramic glaze comprising the following raw materials in parts by weight:

[0031] Component A:

[0032]

[0033] Component B:

[0034]

[0035] The base material in component A includes potassium feldspar, sodium feldspar, dolomite, quartz and calcined talc in a mass ratio of 20:24:18:15:6;

[0036] The concentration of the water glass solution is 10wt%, the concentration of the sodium bicarbonate solution is 20wt%, the concentration of the gadolinium nitrate solution is 0.005mol / L, the concentration of the europium nitrate solution is 0.04mol / L, and the concentration of the silver nitrate solution is 0.07mol / L.

[0037] The method for preparing the ceramic product glaze comprises the following steps:

[0038] S1. Mix the base material and deionized water in a mass ratio of 5:2, ball-mill and sieve to obtain a pretreated base material;

[0039] The mass of the balls in the ball mill is 4 times the mass of the base material; the sieving is through a 200-mesh sieve, and the sieve residue is ≤15%;

[0040] S2, preheat three quarters of the weight of the water glass solution and the sodium bicarbonate solution in a water bath at 90°C for 3 min, mix the two evenly after preheating, then stir at 70°C and 400 r / min for 23 min to obtain a mixed solution A;

[0041] S3, preheat the remaining water glass solution and sodium bicarbonate solution in a water bath at 80°C for 3 min, then add the preheated water glass solution and sodium bicarbonate solution to the mixed solution A and stir at a speed of 150 r / min for 5 min to obtain a mixed solution B, drop nitric acid into the mixed solution B to adjust the pH value of 5, then add the pretreated base material, silver nitrate solution, europium nitrate solution, gadolinium nitrate solution and sodium cocoate in sequence and stir at a speed of 150 r / min for 0.5 h to obtain a mixed solution C, which is the finished product of component A;

[0042] S4. Stir white oil, dimethoxymethyl (3,3,3-trifluoropropyl) silicon, γ-methacryloxypropyl trimethoxysilane, polysiloxane and dodecenyl succinic anhydride at 35° C. for 20 min to obtain a finished product of component B.

[0043] Example 2

[0044] An antibacterial and antifouling ceramic glaze, the ceramic glaze comprising the following raw materials in parts by weight:

[0045] Component A:

[0046]

[0047] Component B:

[0048] 9 parts by weight of dimethoxymethyl (3,3,3-trifluoropropyl) silicon

[0049]

[0050]

[0051] The base material in component A includes potassium feldspar, sodium feldspar, dolomite, quartz and calcined talc in a mass ratio of 35:18:7:20:9;

[0052] The concentration of the water glass solution is 15wt%, the concentration of the sodium bicarbonate solution is 10wt%, the concentration of the gadolinium nitrate solution is 0.008mol / L, the concentration of the europium nitrate solution is 0.03mol / L, and the concentration of the silver nitrate solution is 0.05mol / L.

[0053] The method for preparing the ceramic product glaze comprises the following steps:

[0054] S1. Mix the base material and deionized water in a mass ratio of 5.5:2.3, ball-mill and sieve to obtain a pretreated base material;

[0055] The mass of the balls in the ball mill is 3.5 times the mass of the base material; the sieving is through a 200-mesh sieve, and the sieve residue is ≤15%;

[0056] S2, preheat three quarters of the weight of the water glass solution and the sodium bicarbonate solution in a water bath at 80°C for 4 min, mix the two evenly after preheating, then stir at 95°C and 500 r / min for 20 min to obtain a mixed solution A;

[0057] S3, preheat the remaining water glass solution and sodium bicarbonate solution in a water bath at 85°C for 5 min, then add the preheated water glass solution and sodium bicarbonate solution to the mixed solution A and stir at a speed of 100 r / min for 10 min to obtain a mixed solution B, drop nitric acid into the mixed solution B to adjust the pH value of 6, then add the pretreated base material, silver nitrate solution, europium nitrate solution, gadolinium nitrate solution and sodium cocoate in sequence and stir at a speed of 200 r / min for 1 h to obtain a mixed solution C, which is the finished product of component A;

[0058] S4. Stir white oil, dimethoxymethyl (3,3,3-trifluoropropyl) silicon, γ-methacryloxypropyl trimethoxysilane, polysiloxane and dodecenyl succinic anhydride at 50° C. for 10 min to obtain a finished product of component B.

[0059] Example 3

[0060] An antibacterial and antifouling ceramic glaze, the ceramic glaze comprising the following raw materials in parts by weight:

[0061] Component A:

[0062]

[0063] Component B:

[0064]

[0065] The base material in component A includes potassium feldspar, sodium feldspar, dolomite, quartz and calcined talc in a mass ratio of 27.5:30:12.5:17.5:7.5;

[0066] The concentration of the water glass solution is 20wt%, the concentration of the sodium bicarbonate solution is 15wt%, the concentration of the gadolinium nitrate solution is 0.007mol / L, the concentration of the europium nitrate solution is 0.05mol / L, and the concentration of the silver nitrate solution is 0.06mol / L.

[0067] The method for preparing the ceramic product glaze comprises the following steps:

[0068] S1. Mix the base material and deionized water in a mass ratio of 5.3:2.5, ball-mill and sieve to obtain a pretreated base material;

[0069] The mass of the balls in the ball mill is 5 times the mass of the base material; the sieving is through a 200-mesh sieve, and the sieve residue is ≤15%;

[0070] S2, preheat three quarters of the weight of the water glass solution and the sodium bicarbonate solution in a water bath at 85°C for 5 minutes, mix the two evenly after the preheating, and then stir at 78°C and 450 r / min for 25 minutes to obtain a mixed solution A;

[0071] S3, preheat the remaining water glass solution and sodium bicarbonate solution in a water bath at 90°C for 4 min, then add the preheated water glass solution and sodium bicarbonate solution to the mixed solution A and stir at a speed of 200 r / min for 7.5 min to obtain a mixed solution B, drop nitric acid into the mixed solution B to adjust the pH value of 6, then add the pretreated base material, silver nitrate solution, europium nitrate solution, gadolinium nitrate solution and sodium cocoate in sequence and stir at a speed of 175 r / min for 1 h to obtain a mixed solution C, which is the finished product of component A;

[0072] S4. Stir white oil, dimethoxymethyl (3,3,3-trifluoropropyl) silicon, γ-methacryloxypropyl trimethoxysilane, polysiloxane and dodecenyl succinic anhydride at 42° C. for 15 min to obtain a finished product of component B.

[0073] Example 4

[0074] Application of ceramic glaze:

[0075] The ceramic product glaze component A prepared in Example 3 is made into glaze slurry through conventional procedures, and the glaze is evenly sprayed on the ceramic body and dried. After complete drying, it is fired in a kiln to form a ceramic semi-finished product. The ceramic semi-finished product is evenly sprayed with the ceramic product glaze component B prepared in Example 3 at room temperature and left to stand for 48 hours to obtain a ceramic finished product.

[0076] Example 5

[0077] Application of ceramic glaze:

[0078] The ceramic product glaze component A prepared in Example 2 is made into glaze slurry through conventional procedures, and the glaze is evenly sprayed on the ceramic body and dried. After complete drying, it is fired in a kiln to form a ceramic semi-finished product. The ceramic semi-finished product is evenly sprayed with the ceramic product glaze component B prepared in Example 2 at room temperature and left to stand for 52 hours to obtain a ceramic finished product.

[0079] Example 6

[0080] Application of ceramic glaze:

[0081] The ceramic product glaze component A prepared in Example 1 is made into glaze slurry through conventional procedures, and the glaze is evenly sprayed on the ceramic body and dried. After complete drying, it is fired in a kiln to form a ceramic semi-finished product. The ceramic semi-finished product is evenly sprayed with the ceramic product glaze component B prepared in Example 1 at room temperature and left to stand for 50 hours to obtain a ceramic finished product.

[0082] Comparative Examples 1-3

[0083] Compared with Example 3, the difference is that the weight parts of the gadolinium nitrate solution, the europium nitrate solution and the silver nitrate solution in Comparative Examples 1-3 are as shown in Table 1, and the other operating steps and parameters are the same.

[0084] Table 1

[0085] Gadolinium nitrate solution (parts by weight) Europium nitrate solution (parts by weight) Silver nitrate solution (parts by weight) Comparative Example 2 0 3.7 3.8 Comparative Example 3 3 0 4.5 Comparative Example 4 3 4.5 0

[0086] Comparative Example 4

[0087] Compared with Example 3, the difference is that sodium cocoate is not added in Comparative Example 4, and the remaining operating steps and parameters are the same.

[0088] Comparative Example 5

[0089] Compared with Example 3, the difference is that in Comparative Example 5, dimethoxymethyl (3,3,3-trifluoropropyl) silicon is not added, and the remaining operating steps and parameters are the same.

[0090] Comparative Example 6

[0091] Compared with Example 3, the difference is that no polysiloxane is added in Comparative Example 6, and the remaining operating steps and parameters are the same

[0092] Test Example 1

[0093] According to the detection method in the standard JC / T897-2014, the antibacterial rate of Escherichia coli and Staphylococcus aureus was tested on the ceramic finished products made from the ceramic product glazes prepared in Examples 4-6 and Comparative Examples 1-4 respectively prepared by the preparation method of Example 4, and the results are shown in Table 2.

[0094] Table 2

[0095] Escherichia coli antibacterial rate (%) Antibacterial rate of Staphylococcus aureus (%) Example 1 99.5 99.5 Example 2 99.5 99.6 Example 3 99.7 99.6 Comparative Example 1 83.1 81.9 Comparative Example 2 77.3 74.0 Comparative Example 3 70.8 70.1 Comparative Example 4 89.2 90.4

[0096] It can be seen from Table 2 that the ceramic glaze prepared by the present invention has excellent antibacterial properties. In detail, it can be seen from Comparative Examples 1-3 that, when the total amount of gadolinium nitrate, europium nitrate and silver nitrate remains unchanged, no matter which one is added less, the antibacterial effect on Escherichia coli and Staphylococcus aureus is greatly reduced. This is because the present invention compounded these three, with silver nitrate as the main component and europium nitrate as the auxiliary component, using silver to destroy the proliferation ability of bacteria in a short period of time to induce cell death, and using europium to destroy the sheath and wall structure of bacteria to make the bacteria lose their original functions. On this basis, gadolinium is also used to stimulate the activity of silver and europium ions, so that the antibacterial ability of silver and europium metals is enhanced. That is, the three work together to make the prepared ceramic glaze have excellent antibacterial properties;

[0097] It can be seen from Comparative Example 4 that if sodium cocoate is not added, the antibacterial effect of the ceramic glaze on Escherichia coli and Staphylococcus aureus is reduced to a certain extent. This is because the sodium cocoate added in the present invention forms a micellar structure to wrap the white carbon black in the system, forming a steric hindrance effect, and at the same time, it makes it impossible to form a complete water film on the surface of the white carbon black particles, and the liquid bridge between the particles disappears, which hinders the adsorption of water by the white carbon black, thereby inhibiting the agglomeration between the white carbon black particles, making it uniformly antibacterial, and further enhancing its antibacterial performance.

[0098] Test Example 2

[0099] The anti-fouling grade of the glaze surface of the finished ceramic products made by Examples 4-6 and the ceramic product glazes made by Comparative Examples 5-6 respectively using the preparation method of Example 4 was tested according to standard GB / T3810.14-2016, and the results are shown in Table 3.

[0100] Table 3

[0101] Antifouling grade Example 1 5 Example 2 5 Example 3 5 Comparative Example 5 3 Comparative Example 6 4

[0102] It can be seen from Table 3 that the ceramic product glaze prepared by the present invention has an excellent antifouling effect. Specifically, because the present invention adds dimethoxymethyl (3,3,3-trifluoropropyl) silicon and polysiloxane, the polysiloxane can penetrate and deposit into the micropores on the surface of the ceramic using the glaze prepared by the present invention, and a cross-linking reaction occurs in the system, generating a cross-linked body with a certain hardness and good wear resistance, which can effectively resist the action of external forces and thus achieve a lasting antifouling effect.

[0103] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0104] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An antibacterial and antifouling ceramic glaze, characterized in that: The ceramic product glaze comprises the following raw materials in parts by weight: Component A: Component B:

2. The antibacterial and antifouling ceramic glaze according to claim 1, characterized in that: The base material in component A includes potassium feldspar, sodium feldspar, dolomite, quartz and calcined talc.

3. The antibacterial and antifouling ceramic glaze according to claim 2, characterized in that: The mass ratio of potassium feldspar, sodium feldspar, dolomite, quartz and calcined talc is 20-35:18-30:7-18:15-20:6-9.

4. The antibacterial and antifouling ceramic glaze according to claim 1, characterized in that: The concentrations of the water glass solution and the sodium bicarbonate solution are both 10-20wt%; the concentration of the gadolinium nitrate solution is 0.005-0.008mol / L, the concentration of the europium nitrate solution is 0.03-0.05mol / L, and the concentration of the silver nitrate solution is 0.05-0.07mol / L.

5. A method for preparing the antibacterial and antifouling ceramic glaze according to any one of claims 1 to 4, characterized in that: The method for preparing the ceramic product glaze comprises the following steps: S1, mixing the base material and deionized water uniformly, ball-milling, and sieving to obtain a pretreated base material; S2, preheating three quarters of the weight of the water glass solution and the sodium bicarbonate solution in a temperature-controlled water bath, mixing the two after the preheating is completed, and then stirring at a controlled temperature and speed to obtain a mixed solution A; S3, preheating the remaining water glass solution and sodium bicarbonate solution in a temperature-controlled water bath, then adding the preheated water glass solution and sodium bicarbonate solution to mixed solution A with stirring to obtain mixed solution B and adjusting the pH of mixed solution B, then sequentially adding pretreated base material, silver nitrate solution, europium nitrate solution, gadolinium nitrate solution and sodium cocoate with controlled speed stirring to obtain mixed solution C, which is the finished product of component A; S4, controlling the temperature and stirring white oil, dimethoxymethyl (3,3,3-trifluoropropyl) silicon, γ-methacryloxypropyl trimethoxysilane, polysiloxane and dodecenyl succinic anhydride to obtain a finished product of component B.

6. The method for preparing the antibacterial and antifouling ceramic glaze according to claim 5, characterized in that: In step S1, the mass ratio of the base material to deionized water is 5-5.5:2-2.5; the mass of the balls in the ball mill is 3.5-5 times the mass of the base material; and the sieving is through a 200-mesh sieve with a sieve residue of ≤15%.

7. The method for preparing the antibacterial and antifouling ceramic glaze according to claim 5, characterized in that: In step S2, the temperature of the temperature-controlled water bath preheating is 80-90°C for 3-5 minutes; the temperature-controlled and speed-controlled stirring is specifically to control the temperature at 70-95°C and the speed at 400-500r / min for 20-25 minutes.

8. The method for preparing the antibacterial and antifouling ceramic glaze according to claim 5, characterized in that: In step S3, the temperature of the temperature-controlled water bath preheating is 80-90°C for 3-5 minutes; the stirring speed of adding the preheated water glass solution and sodium bicarbonate solution to the mixed solution A is 100-200 r / min, and the stirring time is 5-10 minutes; the pH of the mixed solution B is adjusted by dripping nitric acid to adjust the pH of the mixed solution B to 5-6; the speed of the speed-controlled stirring is 150-200 r / min, and the time is 0.5-1h.

9. The method for preparing the antibacterial and antifouling ceramic glaze according to claim 5, characterized in that: The temperature of the temperature-controlled stirring in step S4 is 35-50° C. and the time is 10-20 min.

10. An application of the antibacterial and antifouling ceramic glaze according to any one of claims 1 to 4, characterized in that: The application is specifically as follows: first, component A of the ceramic glaze is subjected to conventional processes to prepare glaze slurry, spray glaze, and dry, and then fired into a kiln to form a ceramic semi-finished product; the ceramic semi-finished product is evenly sprayed with component B of the ceramic glaze at room temperature and left to stand for 48-52 hours to obtain a finished ceramic product.

Citation Information

Patent Citations

  • Preparation method of antibacterial ceramic

    CN105272377A

  • Environment-friendly ceramic and preparation method thereof

    CN111233459A

  • Zirconium oxide-based bathroom ceramic and preparation method thereof

    CN115448596A

  • Preparation method of ultra-smooth ceramic glaze

    CN115893844A

  • Anti-doodling and antifouling soft light / matte ceramic tile and preparation method thereof

    CN116640006A

Cited By

  • High-strength antibacterial glaze and preparation process thereof

    CN120136432A

  • High-strength antibacterial glaze and preparation process thereof

    CN120136432B

  • High-performance ceramic glaze for bacteriostatic domestic porcelain and preparation method of high-performance ceramic glaze

    CN120622956A

  • High-performance ceramic glaze for bacteriostatic domestic porcelain and preparation method thereof

    CN120622956B